METODE ANALISIS JALUR DALAM MENGANALISIS KETERGANTUNGAN SMARTPHONE TERHADAP PERILAKU BELAJAR SISWA SMP NEGERI 1 TANTOM ANGKOLA - Wahyudi Yhose A Simanjuntak; Arnah Ritonga (Lembaga Pengembangan Kinerja Dosen, 2023)
The ease of using Smartphones and the many functions that help with activities, make today's teenagers very familiar with Smartphones, including students at SMP Negeri 1 Tantom Angkola. Students tend to use Smartphones for various reasons, such as just wanting to play games and being too active on social media. The impact of Smartphone dependence, especially on student development, will have a negative impact from an academic point of view. The nature of dependence does not just happen, the influence of one another is certainly interconnected or correlated and forms a causal relationship. This paper aims to see how much influence Smartphone dependency has on the learning behavior of students at SMP Negeri 1 Tantom Angkola and which variables have the most influence on the learning behavior of SMP Negeri 1 Tantom Angkola Students. The method used in this study is the Path Analysis method. Path Analysis is a technique for analyzing causal relationships that occur when exogenous variables affect endogenous variables, not only directly but also indirectly. Path Analysis is used to determine the direct and indirect effects of exogenous variables on an endogenous variable which is reflected in the path coefficient. From the research results, it is obtained that the direct influence of social media variables on learning behavior = 44.9%, the large direct influence of online game variables on learning behavior = 40.7%, the direct influence of internet data package variables on learning behavior = 0.4%, the direct effect of school control variables on learning behavior = 85.2%. Then the variable that has the greatest influence on learning behavior is the school control variable with a value of 85.2%.